2018
DOI: 10.1038/s41598-018-34898-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced EPR directed and Imaging guided Photothermal Therapy using Vitamin E Modified Toco-Photoxil

Abstract: Herein we report synthesis, characterization and preclinical applications of a novel hybrid nanomaterial Toco-Photoxil developed using vitamin E modified gold coated poly (lactic-co-glycolic acid) nanoshells incorporating Pgp inhibitor d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as a highly inert and disintegrable photothermal therapy (PTT) agent. Toco-Photoxil is highly biocompatible, physiologically stable PTT material with an average diameter of 130 nm that shows good passive accumulation (2.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In this context, because of their unique optical properties, noble metals such as gold (Au) and silver (Ag) exhibit a well-known photo-physical phenomenon called localized surface plasmon resonance, which contributes to enhancing their intrinsic photo-absorption characteristics 3336. For this reason, they can be functionalized as image-guided photothermal cancer therapy37,38 or PTT agents due to their propensity to generate hyperthermia in tumor cells when irradiated with a laser light 3941. Akin to Au- and Ag-structured nanoparticles, Ti 3 C 2 T x (MXene) nanocomposites, having transition metal element (titanium), exhibit a strong NIR absorption as well as subsequent light-to-heat conversion property resulting in photon-induced hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, because of their unique optical properties, noble metals such as gold (Au) and silver (Ag) exhibit a well-known photo-physical phenomenon called localized surface plasmon resonance, which contributes to enhancing their intrinsic photo-absorption characteristics 3336. For this reason, they can be functionalized as image-guided photothermal cancer therapy37,38 or PTT agents due to their propensity to generate hyperthermia in tumor cells when irradiated with a laser light 3941. Akin to Au- and Ag-structured nanoparticles, Ti 3 C 2 T x (MXene) nanocomposites, having transition metal element (titanium), exhibit a strong NIR absorption as well as subsequent light-to-heat conversion property resulting in photon-induced hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al also reported a hybrid PTT agent, Toco-Photoxil, which consisted of a Pgp inhibitor d-α-tocopheryl PEG 1000 succinate (TPGS), gold nanoparticle and GC-modified poly(lactic-coglycolic acid) (PLGA) for the PTT of tumors (Figure 24a). [153] The gold nanoparticle layer of Toco-Photoxil could be generated via co-ordinate bond formation between gold seeds and the amine group of GC, so that the absorption wavelength of Toco-Photoxil could be tuned for the desired NIR wavelength (750 and 915 nm) in PTT (Figure 24b). Folic-acid-modified Toco-Photoxil (FA-Toco-Photoxil), and IR 780 fluorescent dye-tagged Toco-Photoxils (IR 780-Toco-Photoxil and IR 780-FA-Toco-Photoxil) were prepared for the tumor targeting and in vivo NIRF imaging, respectively.…”
Section: Recent Advances In Theranostic Cnps For Cancer Heterogeneitymentioning
confidence: 99%
“…a–e) Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International license. [ 153 ] Copyright 2018, The Authors, published by Springer Nature.…”
Section: Recent Advances In Theranostic Cnps For Cancer Heterogeneitymentioning
confidence: 99%
“…[52][53][54] ii) More recently, the use of an external trigger combined with NPs has been investigated. This trigger could be ultrasounds, [55][56][57] photothermal therapy, [57][58][59] photodynamic therapy, [57,60,61] or even radiation therapy. [62,63] Most often, the approach consists in targeting the tumor blood vessel using an v 3 peptide to disrupt the neovessels with the external trigger in order to improve the delivery of the drug in a second time ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%